Pengalaman dan Dukungan Keluarga terhadap Perubahan Psikologis Ibu Menopause di Puskesmas Putri Ayu Kota Jambi - Arifarahmi Arifarahmi (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2017)
INTRODUCTION A women up to 45 years old will have menopause phase. Many woman in menopause phase will be psycological changes. In 2013, total of menopause women in Indonesia (45-49 years old) are 17.511.166 womens. In 2014, Jambi has 28.516 woman (45-49 years old). METHOD This research was a descriptive research. The independent variables that researched are experiences and family supported, dependent variables is the psychological changes of menopause woman. The population are womens 50-60 years, in Primary Health Care Putri Ayu are 262 womens. Sampling used simple random sampling of 70 womens. The research was on 25th Mei -06 th juny 2015. RESULTS The researched show many respondent experience in the hard psychology changes as 55,7%, unfavorable experience as 52,9%, and low families support as 60%. CONCLUSIONS AND RECOMMENDATIONS Sugessted to Health center for guidance to all of menopause womens about psychological changes. The increased expectation of menopause womens to their families support to give and care psycological support to the menopause womens. Keyword: psychological changes of menopause, experience, families support